Design Of Multimedia Applications On A Collection Of Prayer Daily Flash Based On Islamic Kids Shoots Kindergardenhope City Bengkulu - Iskandar, Agung Pradana; Sudarsono, Aji (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
This study aims at the implementation of multimedia applications on the multimedia hadist.Aplikasi neighbor hadith produced can provide convenience to teachers Boarding Violating Tarbiyah Cape Betung Kaur in providing materials to students Lessons Hadith.